Biological, social, and healthcare factors for death due to influenza A(H1N1) during the 2009 epidemic in Brazil - Braga, Jose Ueleres; Ribeiro, Ana Freitas (Revista de Saúde Pública, 2024)
OBJECTIVE: To identify risk factors for death from inf luenza A(H1N1), including the effectiveness of the vaccine against influenza A(H1N1) concerning mortality. METHODS: A case-control of incident cases of inf luenza A(H1N1) reported in the epidemiological information systems of the states of São Paulo, Paraná, Pará, Amazonas, and Rio Grande do Sul was conducted. RESULTS: 305 participants were included, 70 of them cases and 235 controls, distributed as follows: Amazonas, 9 cases/10 controls; Pará, 22 cases/77 controls, São Paulo, 19 cases/49 controls; Paraná, 10 cases/54 controls; Rio Grande do Sul, 10 cases/45 controls. These participants had a mean age of 30 years, with 33 years among cases and 25 years among controls. There was a predominance of females both among the cases and controls. Biological (age), pre-existing diseases (congestive heart failure, respiratory disease, and diabetes mellitus), and care factors (ICU admission) associated with death from influenza A(H1N1) were identified. CONCLUSION: The risk factors identified in this investigation not only allowed subsidizing the elaboration of clinical conducts but also indicate important aspects for facing “new” influenza epidemics that are likely to occur in our country.